THE CREATION OF PUBLIC VALUE IN THE PROCESS OF THE DIGITAL TRANSFORMATION OF PUBLIC ADMINISTRATION IN KAZAKHSTAN - Yerlan Abil; Aikyz Bauyrzhankyzy (Public Policy and Administration, 2024)
This paper explores the concept of public value in the context of digital transformation in Kazakhstan’s public administration. It investigates the creation of public value and assesses the outcomes of government digitalization efforts. The study employs a qualitative research methodology, including citizen questionnaires and the analysis of relevant documents. The aim is to not only understand public value creation but also identify the specific dimensions of value in Kazakhstan’s case, filling a gap in the empirical research on public value in Central Asian countries’ digital transformation initiatives.